2012
DOI: 10.1121/1.4769399
|View full text |Cite
|
Sign up to set email alerts
|

When “okay” is not okay: Acoustic characteristics of single-word prosody conveying reluctance

Abstract: The present study explored the acoustic characteristics of prosodic cues that indicate a speaker's reluctance when giving permission or agreement using a single word (“okay”). Eight speakers (four male, four female) produced the recorded materials that were subsequently validated through a listening experiment using 12 normal-hearing listeners. Acoustic analyses revealed that significantly longer word duration was the cue used most consistently across speakers to communicate reluctance. Voice quality, fundamen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Instead, we concentrate on attitudinal aspect (e.g., (b) above). A similar approach is taken by van Zyl and Hanekom (2012). They found the affirmative cue word okay with a neutral agreement to differ prosodically from okay with reluctant agreement within the same discourse position.…”
Section: Aims Questions and Assumptionsmentioning
confidence: 84%
See 1 more Smart Citation
“…Instead, we concentrate on attitudinal aspect (e.g., (b) above). A similar approach is taken by van Zyl and Hanekom (2012). They found the affirmative cue word okay with a neutral agreement to differ prosodically from okay with reluctant agreement within the same discourse position.…”
Section: Aims Questions and Assumptionsmentioning
confidence: 84%
“…In accordance with the claims of Hirschberg and Litman (1993), Ward (2006), van Zyl andHanekom (2012), we assume that the answer to questions (1) is positive. The same applies to question (2).…”
Section: Aims Questions and Assumptionsmentioning
confidence: 97%
“…However, these works all support the–for us–central point that prosody extends far beyond individual syllables or segments into the broader set of organizations supporting language as an embodied behavior that extends across space and time. Changes in prosody can add meaningful valence to single-word utterances (Filipe, Branco, Frota, Castro, & Vicente, 2014; van Zyl & Hanekom, 2013). The suprasegmental organization of prosody might wrap meaningfully around single-word utterances, but perhaps even such brief speech streams allow prosody sufficient time to wrap meaningfully around individual phonemes – and what could be more difficult, around individual phonemes out of proper order.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, other functions require more sophisticated multi-factor analyses for identifying the best disambiguating features. Van Zyl and Hanekom (2012) discovered that okay with a neutral agreement differs in prosody from okay with a reluctant agreement in the same discourse position. Gonen et al (2015) and Hirschberg and Litman (1987 , 1993) found that prosodic information facilitates the hearer distinguishing a discourse marker from its literal counterpart.…”
Section: Review Of Literaturementioning
confidence: 99%